The Door of Mher: The Urartian Deities as Constellations - A. Armin (Babayan)
This article is about the Urartian inscription on the rocky hill named “Door of Mher”, which is located in the vicinity of the modern-day city of Van and on which the pantheon of the Kingdom of Van — the names of deities and the quantities of sacrifices (goat, bull/cow, ram/sheep) prescribed for the deities — is presented, and the quantities of these sacrifices were prescribed during the celebration of the month of Sun. For those involved in Urartian studies, the identities of the deities as well as the logic behind the structure of their sequence have been considered unknown. However, as a result of comparative examination, it turns out that the deities of the Kingdom of Van are first and foremost deity-constellations and, most importantly, they are constructed based on the sequence of the heliacal rising, like the II and IV calendar lists with the Mesopotamian name Mul.Apin.
Keywords: Armenology